MINAT PESERTA DIDIK PEREMPUAN PADA PEMBELAJARAN PJOK KELAS X SMA N 6 SEMARANG - Madia Nur Alisa; Moch Najib Ali; Manarul Hidayat; Agus Wiyanto; Anjar Tri Astuti (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2026)
The purpose of this study is to find out the interest of female students at SMA Negeri 6 Semarang in Physical Education, Sports, and Health (PJOK) learning. The type of this research is descriptive research with the population being female students of class X at SMA Negeri 6 Semarang, with the research sample consisting of 62 students. Interest can also be interpreted as a sense of attraction to certain activities without coercion. The technique used for data collection in this study is through questionnaires. The descriptive statistical data analysis in this study uses Microsoft Excel. From the data analysis conducted, according to the research results, the interest of students in participating in PJOK learning at SMA N 6 Semarang shows that 10 students (16.13%) have a very high interest in learning sports, 48 students (77.42%) show high interest, 4 students (6.45%) have low interest, and no students show interest that falls intovery low category. From this data, it can be concluded that the interest of female students in PJOK learning in Grade X at SMA Negeri 6 Semarang falls into the High category.